Low Th2 and high PD1+ TFh cells in blood predict remission after CTLA-4Ig treatment for 48 weeks in early rheumatoid arthritis - Tilia Selldén; Kerstin Andersson; Inger Gjertsson; Anna-Karin Hultgård Ekwall; Kristina Lend; Merete Lund Hetland; Mikkel Østergaard; Tillmann Uhlig; Marte Schrumpf Heiberg; Michael T. Nurmohamed; Jon Lampa; Tuulikki Sokka Isler; et al. (PLoS ONE, 2025)
Objective To determine whether baseline CD4+ T helper (Th) cell subset proportions in blood may serve as predictive biomarkers for achieving remission 48 weeks after initiating CTLA-4Ig, anti-tumor necrosis factor (TNF), or anti-interleukin 6 receptor (IL6R) treatment in patients with early rheumatoid arthritis (eRA). Methods This study included 60 untreated eRA patients from the larger randomized treatment trial NORD-STAR. They were treated with methotrexate (MTX) combined with either CTLA-4Ig (n = 17), anti-TNF (n = 22), or anti-IL6R (n = 21). Disease activity was assessed by clinical disease activity index (CDAI), C-reactive protein, and erythrocyte sedimentation rate. The primary outcome was remission (CDAI ≤ 2.8) at week 48, and the secondary outcomes were time to reach remission or sustained remission during the 48-week follow-up. CD4+ T cell subset proportions were analyzed fresh by flow cytometry at baseline and at 24 and 48 weeks. Results In CTLA-4Ig + MTX-treated patients, baseline Th2 together with PD1+ T follicular helper (TFh) cell proportions predicted CDAI remission at week 48 (AUC: 0.986, 95% CI 0.94–1.0). Survival analysis revealed that patients with Th2 proportions below 16.8% or PD1+ TFh proportions above 7.6% at baseline were more likely to achieve remission (log-rank p = 0.002 and p = 0.007, respectively), and sustained remission (log-rank p = 0.01 and p = 0.001, respectively), over the 48-week follow-up. CD4+ T cell subset proportions did not predict remission in patients treated with anti-TNF + MTX or anti-IL6R + MTX. Only CTLA-4Ig treatment reduced PD1+ TFh and PD1neg TFh fractions after 48 weeks. Conclusion Circulating Th2 and PD1+ TFh cell proportions at baseline may serve as predictive biomarkers for achieving CDAI remission after 48 weeks of CTLA-4Ig treatment in eRA.